Russell’s viper envenomation endocrinopathies among Bangladeshi victims: Unlikely or under-recognized? (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2024)
Abstract not available J Assoc Clin Endocrinol Diabetol Bangladesh, July 2024;3(2): 65-66